Controllability of coupled systems for impulsive φ-Hilfer fractional integro-differential inclusions. Issue 2 (22nd January 2022) - Boudjerida, A.; Seba, D.; N'Guérékata, G. M.
ABSTRACT: This paper studies the controllability of a coupled system for a class of impulsive fractional integro-differential inclusions involving φ -Hilfer fractional derivative and subject to coupled nonlocal integral initial conditions in the case of convex set-valued maps. Some auxiliary conditions are introduced in order to apply a fixed point theorem due to Bohnenblust–Karlin. An illustrative example is provided to exemplify our theoretical results.